KEY STAGES OF FORMING INDIVIDUAL STYLE MELETIY KICHURA’S - Касіян, Л. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article attempts to characterize the key stages of the formation of the individual style of Meletiy Kichura. Dynamic self-organization of the individual style of the author from imitation to his own creative manner is analyzed. It is proved that satirical attitude is the dominant author's stylistic quest.